Massification of streaming audiovisual content audiences on the Netflix and Disney Plus platforms in the context of COVID-19 (years 2020 to 2022) - Zaray De Los Ángeles Rumbos Pérez (My University, 2024)
The COVID-19 confinement affected the entertainment industry from production to distribution, causing methods to change to maintain audiovisual content consumers as subscribers. Streaming platforms were a solution, allowing access to entertainment from home with varied and original content.
Masificación de audiencias de contenido audiovisual de streaming en las plataformas Netflix y Disney Plus en el contexto de COVID-19 (años 2020 a 2022)